1990
DOI: 10.1111/j.1755-3768.1990.tb01919.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes 2 1/2 years after extracapsular cataract extraction with implantation of a posterior chamber lens

Abstract: Morphological changes and lens position were examined in 51 eyes of 51 patients 25 to 37 (mean 31) months after extracapsular cataract extraction with implantation of a posterior chamber lens in the ciliary sulcus. Ocular morphology was compared to a previously published examination of the same eyes performed 4 months after surgery. The anterior chamber depth, lens position and the position of the posterior lens capsule had remained unchanged. 'Iris bulging', i.e. a gonioscopically visible slight impression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…1995). We reported rates of 5.5−6.1% in the other three sites, which is similar to contemporary findings in a UK survey (5.0%) (Desai 1993a) and reports from single Danish clinics (3.9% and 5.2%) (Naeser et al. 1990; Wegener et al.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1995). We reported rates of 5.5−6.1% in the other three sites, which is similar to contemporary findings in a UK survey (5.0%) (Desai 1993a) and reports from single Danish clinics (3.9% and 5.2%) (Naeser et al. 1990; Wegener et al.…”
Section: Discussionsupporting
confidence: 90%
“…The results seem valid as the reported USA rate of rupture of 1.9% was similar to two contemporary US studies reporting rates of 2.2% (Holland et al 1992) and 2.5% (Willerscheidt et al 1995). We reported rates of 5.5)6.1% in the other three sites, which is similar to contemporary findings in a UK survey (5.0%) (Desai 1993a) and reports from single Danish clinics (3.9% and 5.2%) (Naeser et al 1990;Wegener et al 1998). Rates have improved in Denmark and are currently much lower, at 0.5% (http://www.katbase.dk).…”
Section: Perioperative Complicationssupporting
confidence: 87%
“…Corneal oedema, CME and ARMD were the reason for poor vision, The VA was slightly better by ECCE than by ICCE but not statistically significant. Naeser et al (1990) and Calissendorff & Boos (1990) also did not find any difference. Our gonioscopic study showed that nearly all the haptics rested on the ciliary body band, and as reported by Reidy et al (1985) most haptics of ACLs do.…”
Section: Discussionmentioning
confidence: 75%
“…Also Naeser et al (1990) had all corneal oedema cases among the ICCEs. CME appeared in our ICCE-cases and this corresponds to the findings of Naeser et al (1990).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation